Russian and foreign legislation on regulation of post approval variations in the dossier for the medicinal products - Yu. V. Olefir; V. A. Merkulov; E. A. Soloviev; E. A. Ustyugova; L. V. Sayapina; V. P. Bondarev (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Drug licensing is the most crucial factor for effective market regulation of pharmaceuticals. The rapid development of the pharmaceutical industry, emergence of new scientific data, and changes in composition of medicinal products drive the need for introduction of variations in original registration dossiers. The process of such variation approval implemented in a particular country is the key factor in assessing the effects of the variation on the quality, safety and efficacy of the medicinal product, and sets a timelines for their realization. The present article describes existing classifications of variations, which are adopted in the European Union (EU), USA and Russia. Also the article concerns the upcoming changes in Russia in the scope of Eurasian Economic Union establishment and the necessity of harmonizing the procedure with the European Union.